Teacher development in action: an empirically-based model of promoting conceptual change in in-service language teachers in Slovakia - Kubanyiova, Magdalena (2007)
This longitudinal mixed methods study concerns the professional development of eight non-native English as a foreign language (EFL) teachers in Slovakia. Raising awareness of the teacher's role in creating conducive learning environments has not traditionally been part of the aims of EFL teacher education programmes. This study therefore set out to explore the impact of a 20-hour experiential in-service teacher development course that had been informed by theoretical principles drawn from within as well as outside the domain of applied linguistics, including second language motivation research, group dynamics and educational psychology. A combination of quantitative measures (pre- and post-test questionnaires measuring students' perceptions of their classroom environment) and qualitative measures (interviews, observations, and written course feedback) were employed to assess the course impact on the teachers' conceptual change. The results show that although some traces of impact were found in the participants' teaching practice, conceptual change did not occur despite their positive appraisals of the programme. Further interrogation of qualitative data about the reasons for this outcome has led to the generation of an integrated model of Language Teacher Conceptual Change (LTCC), which accommodates and thus interprets the variable and individual ways in which the eight teachers responded to the course input. The fact that the complex and idiosyncratic growth patterns fitted comfortably into the proposed conceptual framework provides validation for the theoretical construct, and the LTCC model is therefore believed to offer an integrated, theoretically-informed and empirically-grounded framework for future research on language teacher development and for designing effective teacher education interventions.